Karya Penyelamatan Yesus dan Kebebalan Manusia Pendosa Menurut Lukas 23:39 - Gulo, Yarnida (SEKOLAH TINGGI TEOLOGI STAR'S LUB LUWUK BANGGAI, 2024)
This article discusses human obstinacy towards sin and the blasphemy against Jesus Christ based on Luke 23:39, with the aim of providing a theological understanding of Jesus' crucifixion and its relevance to the lives of believers. The research employs a literature review method to examine theological literature, books, journals, and primary sources. The findings indicate that sin has a strong influence that causes human obstinacy, leading to blindness to truth and goodness, as seen in the criminal crucified alongside Jesus. This obstinacy prevents individuals from recognizing the salvation offered through Jesus Christ. The research emphasizes the importance of confessing sins and repentance as the path to salvation and peace with God. Jesus' crucifixion is a redemptive act that brings freedom, peace, and joy to those who believe and accept Him. In conclusion, believers must live in repentance and accept salvation from Jesus.